Challenges for the protection of unaccompanied foreign minors in the streets of Ceuta - García-España, Elisa; Carvalho da Silva, Jacqueline (My University, 2019)
Ceuta, as a Spanish enclave in Africa face specific challenges in terms of immigration. Due the proximity of Ceuta and Morocco, the residents of Moroccan provinces adjoining are exempted from visa requirements and can be authorized to enter and exit the Spanish city, on a daily basis, but not the rest of the national territory. A number of the people that cross this border are minors, many of them come from adjoining provinces and enter legally, with their passports, accompanied by their parents or a relative who abandon them in Spanish territory, with the aim that they could get a better life and help their family economically. Others come from other provinces and undertake this trip alone, often with the same responsibility, of helping their family, and stay on the land border between Morocco and Spain for days or even months trying to sneak across the border illegally. These minors scape from the system, they are unprotected, exposed to criminal and victimological risk. Besides, their presence on the streets generate a sense of public insecurity and social alarm, although the crime rate of this group is low, negative labels are applied to them. In this context, Ceuta, specifically the Department of Health, Social Affairs, Minors and Equality, has signed an agreement with the University of Málaga, implemented by the Observatory of the Crime control system towards Immigration (OCSPI), to develop a pilot project of research and social intervention to prevent juvenile delinquency and protect these minors.
Keywords: Extranjeros; Menores; Crimen; Prevención; Protección; Sociología -- Congresos; Foreign; Unaccompanied minors; Crime; Prevention; Protection